The role of Tiktok branded augmented reality advertisement towards eWOM and attitude towards brand - Azmarisya Hanifa; Dedi Kurniawan (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
TikTok is a video-sharing social networking platform that allows users to create and share 15-second videos from genres like dance, comedy, and education. One feature of TikTok is the Branded Augmented Reality Advertisement, which enables advertisers to add virtual shareable stickers, filters, and customized special effects to their real-life video advertisements. Studies on Augmented Reality Advertisements are still lacking. This research examines the influence of credibility, lack of irritation, informativeness, and entertainment on eWOM in Tiktok Branded Augmented Reality Advertisement. It also investigates the influence of eWOM on attitude towards the brand. This study employs a quantitative method with a survey technique. The convenience sampling technique is used, and the questionnaire is filled up by 282 valid respondents from Tiktok users living on Java Island, Indonesia. Data is collected using online questionnaires distributed via social media and messaging apps. The structural equation modelling technique is employed for data analysis using SPSS and AMOS applications. The research found that credibility and entertainment in Tiktok Branded Augmented Reality Advertisement significantly affect eWOM. Also, eWOM significantly impacts attitude toward the brand. However, the lack of irritation and informativeness do not significantly influence eWOM.